2012
DOI: 10.18438/b86311
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Publishing Patterns at a Large Research University: Implications for Library Practice

Abstract: 2012 Amos, Mower, James, Weber, Yaffe, and Youngkin. This is an Open Access article distributed under the terms of the Creative Commons-Attribution-Noncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/by-nc-sa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Published case studies provide further insight into new services launched since 2003 by academic and research libraries in Germany (Ball & Tunger, 2006), Australia (Drummond & Wartho, 2009;Gibbs & Sergeant, 2009), and the United States (Hendrix, 2010), as well as a whole department devoted to bibliometrics in Austria (Gumpenberger et al, 2012), and smaller scale or one-off activities and undertakings in the United Kingdom (Delasalle, 2012) and United States (Amos et al, 2012;Bennett, Leonard, & Wrublewski, 2012). Activities undertaken range from impact analysis (described as "response analysis" by Ball and Tunger, 2006), using quality indicators such as the h-index, Egghe's g-index, or alternative calculations for humanities and social science researchers (Bennett et al, 2012;Delasalle, 2012: Drummond & Wartho, 2009Hendrix, 2010), to trend analysis for scientific topics over time (Ball & Tunger, 2006;Drummond & Wartho, 2009), in addition to delivery of training and education for individuals and groups, which at the University of Vienna includes curricular courses for doctoral students and LIS students (Gumpenberger et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Published case studies provide further insight into new services launched since 2003 by academic and research libraries in Germany (Ball & Tunger, 2006), Australia (Drummond & Wartho, 2009;Gibbs & Sergeant, 2009), and the United States (Hendrix, 2010), as well as a whole department devoted to bibliometrics in Austria (Gumpenberger et al, 2012), and smaller scale or one-off activities and undertakings in the United Kingdom (Delasalle, 2012) and United States (Amos et al, 2012;Bennett, Leonard, & Wrublewski, 2012). Activities undertaken range from impact analysis (described as "response analysis" by Ball and Tunger, 2006), using quality indicators such as the h-index, Egghe's g-index, or alternative calculations for humanities and social science researchers (Bennett et al, 2012;Delasalle, 2012: Drummond & Wartho, 2009Hendrix, 2010), to trend analysis for scientific topics over time (Ball & Tunger, 2006;Drummond & Wartho, 2009), in addition to delivery of training and education for individuals and groups, which at the University of Vienna includes curricular courses for doctoral students and LIS students (Gumpenberger et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Services can be targeted at individuals, academic units, or institutional level and marketed in various ways for internal or external purposes: for example, advice on publishing strategies, especially for early-career researchers, and support for job applications or a salary/faculty review (Delasalle, 2012;Drummond & Wartho, 2009); "tenure metrics" workshops for faculty (Hendrix, 2010); standard sets of research impact measures for "grant application statements" (Drummond & Wartho, 2009); output comparisons for benchmarking with peer groups at different institutions (Ball & Tunger, 2006;Bennett et al, 2012;Delasalle, 2012;Drummond & Wartho, 2009); analyzing publishing patterns and usage data to inform a scholarly communications program at the University of Utah (Amos et al, 2012); finding a university's most cited papers and providing h-indices for the most cited researchers for institutional promotional materials (Hendrix, 2010); and support for national research assessment exercises (Delasalle, 2012;Drummond & Wartho, 2009), including compiling whole-career citation counts for researchers across the university (Gibbs & Sergeant, 2009). Practitioners have identified additional benefits of bibliometrics work in informing library collection development, facilitating institutional repository growth and improving metadata quality but also comment on the significant staffing effort involved (Amos et al, 2012;Drummond & Wartho, 2009;Gibbs & Sergeant, 2009;Hendrix, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the only U.S. bibliometric study found involving OA publishing, Amos et al () reported that 1% of the articles published by 22 “prolific” researchers at the University of Utah were published in OA journals. It is clear that additional local and multi‐institutional studies are needed to gauge changes in scholarly publishing.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some larger bibliometric studies conducted to quantify OA publishing in India, 5 Germany, 6 and the UK, 7 but essentially none in the United States. In a study of 22 "prolific" researchers at the University of Utah, Amos et al 8 found only 1% of those researchers published in an OA journal. In a larger study of ARL libraries, Hubbard 9 reported that annual Gold OA publishing was between 5% and 9% for the institutions studied.…”
Section: Literature Reviewmentioning
confidence: 99%